2014
DOI: 10.5185/amlett.2014.amwc.1038
|View full text |Cite
|
Sign up to set email alerts
|

Development Of Nanocomposites Based On Polypyrrole And Carbon Nanotubes For Supercapacitors

Abstract: Supercapacitors are recognized as one of the most promising energy storage devices for a wide range of civilian and military applications in electric vehicles, uninterruptible power supplies. Conducting polymer nanocomposites are new functional materials suitable for supercapacitors due to synergistic effect of individual components. In present work, polypyrrole/CNT nanocomposites have been prepared by an in-situ chemical polymerization method and studied for supercapacitor. CNTs were well functionalized using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…24 The peak appearing at 680 cm −1 corresponds to ring deformation. 26 It is observed that all the peaks appearing in the fingerprint region of PPy are also observed in the FTIR spectra of PPy/MWCNT nanocomposites. This indicates that the main constituents of PPy and its nanocomposite with MWCNTs have the same chemical structure.…”
Section: Characterisations Of Samplesmentioning
confidence: 88%
“…24 The peak appearing at 680 cm −1 corresponds to ring deformation. 26 It is observed that all the peaks appearing in the fingerprint region of PPy are also observed in the FTIR spectra of PPy/MWCNT nanocomposites. This indicates that the main constituents of PPy and its nanocomposite with MWCNTs have the same chemical structure.…”
Section: Characterisations Of Samplesmentioning
confidence: 88%
“…The band at 1291 cm −1 is related to the C-N in-plane, and the bands at 1175 and 1042 cm −1 are associated to the C-H bending modes while the band for C-H out-of-plane deformation vibration was observed at 898 cm −1 [29]. The peaks at 672 cm −1 corresponding to ring deformation, 948 cm −1 corresponding to C-H deformation [33]. It was observed that all the spectra contain a very weak but broad adsorption band in the region between 2500 cm −1 to 3500 cm −1 , which is commonly assigned for the adsorption band of O-H, C-H, N-H groups [20].…”
Section: Characterization Of Ppy-mwcnt Nanocompositementioning
confidence: 96%
“…500µL pyrrole was slowly added drop wise and the polymerization was allowed to continue for 4 h with constant stirring. The precipitated composite was filtered, washed thoroughly with de-ionized water and then dried to get PPy/MnO2 nanocomposite [17]. The similar procedure was carried out for 10% and 15% MnO2.…”
Section: Synthesis Of Polypyrrole and Polypyrrole/mno2 Nanocompositesmentioning
confidence: 99%